2012
DOI: 10.3390/nu4070648
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Cancer: Implications for LIV-1 in Breast Cancer

Abstract: Zinc is a trace mineral which is vital for the functioning of numerous cellular processes, is critical for growth, and may play an important role in cancer etiology and outcome. The intracellular levels of this mineral are regulated through the coordinated expression of zinc transporters, which modulate both zinc influx as well as efflux. LIV-1 (ZIP6) was first described in 1988 as an estrogen regulated gene with later work suggesting a role for this transporter in cancer growth and metastasis. Despite evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 190 publications
1
102
0
2
Order By: Relevance
“…This protein may play a role in both cell growth, by acting as a zinc transporter, as well as the induction of metastasis, by association with matrix metalloproteinases. 41 It is worth mentioning that this transporter protein is also detected in neoplastic breast tissue.…”
Section: Author(s) Study Design Resultsmentioning
confidence: 99%
“…This protein may play a role in both cell growth, by acting as a zinc transporter, as well as the induction of metastasis, by association with matrix metalloproteinases. 41 It is worth mentioning that this transporter protein is also detected in neoplastic breast tissue.…”
Section: Author(s) Study Design Resultsmentioning
confidence: 99%
“…In various studies, it was found that the serum levels of trace elements in patients with BC have changed and although their role is not fully understood, it may be associated with the risk of this disease (8). Zinc (Zn) is a vital mineral for the operation of numerous cellular processes and growth and may play an important role in malignancy etiology and outcome (9). This mineral has an excessive accumulation in BCs and malignant cell lines compared with normal mammary epithelium (10).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of applying The animals' body weight in particular weeks of the experiment are presented in Table 2. Carcinogen treatment did not result in any loss of appetite of the animals, which is evidenced by a greater increase in body weight (week [7][8][9][10][11][12][13][14][15][16][17][18][19] in the group that obtained Cu plus resveratrol (p < 0.001), and no differences in body weight observed in the remaining supplemented groups; increases in body weight were significantly lower in rats fed standard diet (unsupplemented group), as compared with the non-DMBAtreated group (p < 0.005) (Table 3). However, no weight loss was found in the rats of any of the examined groups (Tables 2, 3).…”
Section: Resultsmentioning
confidence: 99%